Pengaruh Model Pembelajaran STAD Berbantuan Media Spinning Wheel terhadap Pemahaman Siswa Materi Cerpen Kelas V SDN 3 Riau silip - Madiya Rosilawati; Romadon; Yorenza Meifinda (JPUS: Jurnal Pendidikan Untuk Semua, 2026)
This research is motivated by the lack of students' understanding of short story material. Because the learning process still uses the lecture method when delivering learning materials, varied and innovative learning models and media have not been applied. The goal of this study was to find out how the STAD learning model, which includes spinning wheel media, helped students in class V SDN 3 Riau Silipunderstand what they were learning about short stories. The research method used is the pre-experimental design method with one-group pretest-posttest design. The sample collection technique is saturated sampling and the data collection technique is a test. The data analysis technique uses a normality test in the form of a Saphiro Wilk test and a hypothesis test using a paired sample T-test. Based on the results of the study, the normality test on the pretest with sig. of 0.527> 0.05 and posttest of 0.385> 0.05, so the data is normally distributed. The results of the hypothesis test using the paired sample T-Test with a sig value of 0.000 <0.05. This shows that Ho is rejected and Ha is accepted. It can be concluded that the STAD learning model assisted by spinning wheel media has an effect on students' understanding of short story material in grade V of SDN 3 Riau Silip.